Building Bridges: Teaching Programming through Problem-Based Learning in Mechanical Engineering - Sravanthi, C.; Dharmavarapu, Pratibha; Neeraja, A. (Journal of Engineering Education Transformations, 2025)
Teaching programming to mechanical engineering students, often seen as a computer science endeavor, requires a thoughtful approach to highlight its relevance in their field. The mechanical engineering teacher can bridge this gap by demonstrating how programming solves complex engineering problems. Using real-world examples such as simulating mechanical systems or automating data analysis, illustrates the practical benefits of programming skills. To engage students, the teacher implemented Problem-Based Learning (PBL) activities tailored to mechanical engineering contexts. Activities like “Trace it Out,” where students identify code errors, and “Jumble the Code,” which involves ordering or debugging code pieces, help students connect programming concepts to engineering projects. Solutions to real-world problems are presented as poster presentations, making learning interactive and hands-on. Community problems and solutions were documented and assessed using designed rubrics, reinforcing programming knowledge and developing problem-solving skills. Regular feedback and project-based assessments, rather than traditional exams, better measure students’ understanding and ability to apply programming skills to engineering problems. This comprehensive approach—linking programming with mechanical engineering applications, mentoring, active learning, and continuous feedback—transforms students’ perspectives, helping them realize the invaluable role of programming in their professional development as mechanical engineers. Providing access to online resources and encouraging participation in coding communities further enhances their learning experience.